Cloud computing security mechanisms random number authentication - Yadav, Amitabha (Edelweiss Applied Science and Technology, 2025)
Cloud computing security is an important aspect that has received extensive research attention because of the increasing use of cloud based services. Field of cloud computing security is continually evolving. Cloud security points towards the group of practices, technologies, rules, and procedures that are kept in place to secure data, applications, and services which are deployed on cloud computing platforms. Cloud computing give permission to organizations and individuals to keep, process, and get data and applications over the internet, but this convenience also initiates new security challenges. Cloud security aims to address the issues and assure the confidentiality, integrity, and availability of cloud services. Cloud security aspects are included in the paper. Boundary level protection framework using honey pot encryption technique is proposed in the paper. How threats are attacking at the boundary level of cloud is discussed. Cloud security framework is proposed in this paper. The author attempts to propose a security mechanism named as Random Number Authentication for the system.